Flexible full-biodegradable Janus nanofiber membrane for oil-water separation and preparation of flexible full-biodegradable Janus nanofiber membrane

By preparing Janus-structured nanofiber membranes, the problems of insufficient hydrophilicity and hydrophobicity and non-degradability of nanofiber membranes in oil-water separation were solved, achieving efficient and environmentally friendly oil-water separation.

CN121087699APending Publication Date: 2025-12-09HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511486736.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing nanofiber membranes have problems in the field of oil-water separation, such as difficulty in achieving both hydrophilic and hydrophobic properties, non-degradability, and insufficient mechanical flexibility, resulting in poor separation performance and environmental pollution.

Method used

Janus-structured fibers were prepared by parallel electrospinning using two biodegradable polymer spinning solutions, and then hydrophilically modified to form nanofiber membranes with good flexibility and biodegradability.

Benefits of technology

It achieves efficient oil-water separation, mechanical flexibility lifting, and complete biodegradability, making it suitable for separating complex oil-water mixtures and meeting environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121087699A_ABST
    Figure CN121087699A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible full-biodegradable Janus nanofiber membrane for oil-water separation, which is characterized in that two degradable polymer spinning solutions are spun into a composite nanofiber membrane with a Janus structure through a side-by-side electrostatic spinning method, and then hydrophilic modification is performed to obtain a hydrophilic nanofiber membrane used as an oil-water separation membrane. The product is the flexible full-biodegradable Janus nanofiber membrane for oil-water separation. The obtained hydrophilic nanofiber membrane has good mechanical flexibility, full biodegradability and excellent oil-water selective permeability, the oil-water separation effect and application stability are remarkably improved, the service life is remarkably prolonged, and the hydrophilic nanofiber membrane will become an oil-water separation membrane material with practical value.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of Janus nanofiber membrane, in particular to a flexible full-biodegradable Janus nanofiber membrane for oil-water separation, and preparation of the fiber membrane. BACKGROUND

[0002] Oil-water separation technology, as one of the core supporting technologies for upgrading of petroleum and chemical production and environmental protection, has been widely used in industrial wastewater deep treatment, oilfield exploitation of oily wastewater recovery, marine oil spill emergency cleaning and other key scenes, and its separation efficiency and environmental protection performance are directly related to resource recycling and ecological environment safety.

[0003] With the diversified development of industry, the oil components in oil-water mixture are increasingly complex (such as emulsified oil containing surfactant, high viscosity heavy oil, etc.), and the adaptability of traditional separation methods to such complex systems has decreased significantly, therefore, developing new oil-water separation materials with high separation performance and green environmental protection properties has become a key research direction in the fields of material science and environmental engineering.

[0004] Among many new separation materials, nanofiber membranes have shown irreplaceable application potential in the field of oil-water separation due to their unique structural advantages. Specifically, the outstanding advantages of nanofiber membranes include: ultra-large specific surface area can provide sufficient separation active sites, high porosity can effectively reduce liquid permeation resistance, and by adjusting the preparation process, the structure parameters such as fiber diameter and pore size distribution can be precisely adjusted. However, the development of nanofiber membranes in the field of oil-water separation still faces three major technical challenges: first, single-component nanofiber membranes are often difficult to simultaneously possess hydrophilic and hydrophobic (or oleophilic and oleophobic) properties due to their own chemical composition, resulting in poor separation effect for multi-phase oil-water mixtures (such as oil-water-solid impurity system, multiple emulsified oil system) in complex environments, and cannot meet the diversified needs of actual scenes; second, most of the existing nanofiber membranes with excellent performance are made of non-degradable polymer materials (such as polypropylene, polyvinylidene fluoride, etc.), which can easily form solid waste pollution after use, and are difficult to meet the environmental friendliness requirements of the global "double carbon" target and environmental protection; third, some nanofiber membranes with good separation performance have insufficient mechanical flexibility, which can easily be damaged during bending, folding and other actual operations, affecting their service life and application stability.

[0005] In summary, developing a new type of nanofiber membrane material that integrates high separation capacity, full biodegradability and excellent mechanical flexibility has become a key breakthrough for breaking through the current bottleneck of oil-water separation technology and promoting the green and sustainable development of the field, and is also a research hotspot that the academic and industrial circles are concerned about. SUMMARY

[0006] The present application aims at the deficiencies of nanofiber membranes in the field of oil-water separation, and provides a nanofiber membrane with good flexibility, biodegradability and oil-water selective permeability, which is prepared by spinning two kinds of compatible degradable polymer spinning solutions through double-channel side-by-side electrospinning, spinning Janus structure fibers with different components on both sides, and then performing hydrophilic modification to obtain a fully biodegradable Janus nanofiber membrane suitable for efficient oil-water separation application.

[0007] To achieve the above-mentioned purpose, the flexible fully biodegradable Janus nanofiber membrane for oil-water separation provided by the present application is prepared by spinning two kinds of degradable polymer spinning solutions through side-by-side electrospinning method to spin a composite nanofiber membrane with Janus structure, and then performing hydrophilic modification to obtain a hydrophilic nanofiber membrane for oil-water separation, i.e., a flexible fully biodegradable Janus nanofiber membrane for oil-water separation; The two kinds of degradable polymers selected for the spinning solution are any two kinds of poly(lactic acid) (PLA), poly(epsilon-caprolactone) (PCL), poly(butylene succinate) (PBS), poly(3-hydroxyalkanoate) (PHA), poly(butylene adipate-co-terephthalate) (PBAT), poly(3-hydroxybutyrate) (PHB), poly(acrylic acid) (PAA) and poly(vinyl alcohol) (PVA) that can smoothly perform side-by-side electrospinning, and the solvent selected for the spinning solution is at least one of N,N-dimethylformamide (DMF), dichloromethane (DCM), N-methyl pyrrolidone (NMP), hexafluoroisopropanol (HFIP), N,N-dimethylacetamide (DMAC), chloroform and carbon tetrachloride. The hydrophilic modifier used for the hydrophilic modification is prepared from a compound containing a hydrophilic group by using an initiator, and the compound containing a hydrophilic group is at least one of 1-vinyl-2-pyrrolidone (NVP), acrylic acid (AA), acrylamide (AM), vinyltriethoxysilane (VTES), acrylamide and chloroacetic acid.

[0008] To make the nanofiber membrane meet the requirement of full biodegradability, the present application selects two kinds of compatible degradable polymers to prepare the spinning solution, and the selection of the two kinds of polymers not only meets the requirement of side-by-side electrospinning, but also enhances the mechanical properties of the nanofiber, so that the nanofiber has better tensile control ability. The two kinds of polymer spinning solutions are spun into Janus structure fibers, so that the chemical or physical properties of the fiber surface are asymmetric to adapt to the application of oil-water separation. In addition, the composite nanofiber membrane is further subjected to hydrophilic modification to obtain hydrophilicity, thereby improving the efficiency of the oil-water separation application. The finally obtained hydrophilic nanofiber membrane has good mechanical flexibility, full biodegradability and excellent oil-water selective permeability, and the oil-water separation effect, application stability and service life are significantly improved, so that the hydrophilic nanofiber membrane will become an oil-water separation membrane material with practical value.

[0009] As a limitation of the above technical solution, the two degradable polymers selected for the spinning solution are polylactic acid PLA and polybutylene adipate terephthalate PBAT; and / or, the solvent selected for the spinning solution is a mixed solvent prepared from hexafluoroisopropanol HFIP and N,N-dimethylformamide DMF.

[0010] As a limitation of the above technical solution, the solvent selected for the spinning solution is a mixed solvent prepared from hexafluoroisopropanol HFIP and N,N-dimethylformamide DMF in a volume ratio of 9:1.

[0011] The optimal solution of the present application uses PLA as the main degradable polymer material of the Janus structure fiber, selects the degradable polymer PBAT which is compatible with PLA in terms of electrospinning requirements and mechanical properties, effectively neutralizes the mechanical properties of PLA using the good flexibility provided by PBAT, effectively improves the stability of the spinning process, and optimizes the performance of the final product. For the selection of the solvent of the spinning solution, the mixed solvent of HFIP and DMF is selected, and the same solvent is used for the spinning solution of the two polymers, which not only effectively solves the problem of needle blockage in the spinning process, but also significantly improves the stability of the spinning.

[0012] As a limitation of the above technical solution, the concentration of the two degradable polymers in the spinning solution is 100mg / mL ~220mg / mL.

[0013] As a limitation of the above technical solution, the hydrophilic modifier is prepared by adding vinyl triethoxysilane VTES and 1-vinyl-2-pyrrolidone NVP to the reaction solvent N,N-dimethylacetamide DMAC, stirring thoroughly, then adding an initiator, and then heating to 80~100℃ for continuous reaction; as a preferred, the amount of vinyl triethoxysilane, 1-vinyl-2-pyrrolidone, N,N-dimethylacetamide and initiator is 1~5g:2~6g:100~200mL:0.1~1g.

[0014] As a limitation of the above technical solution, the initiator is selected from one of hydrogen peroxide H2O2, sulfur tetrafluoride SF4, azobis isopropyl cyanide AIVN, azobis isobutyronitrile AIBN, ammonium persulfate APS, benzoyl peroxide BPO and dicumyl peroxide DCP.

[0015] The concentration of the two polymer spinning solutions and the preparation conditions of the hydrophilic modifier are optimized to optimize the performance of the hydrophilic nanofiber membrane.

[0016] As a limitation of the above technical solution, the side-by-side electrospinning conditions are a voltage of 10~15KV, a pushing speed of 0.8~1.5mL / h, a double-needle pushing speed ratio of 1:1, a receiving distance of 15~20cm, and a drum rotation speed of 300~600rpm.

[0017] Further improve and parallel electrospinning conditions, especially require the same in the process control two injector push speed to keep the same, to achieve two polymer in the fiber Janus structure, rather than mixed.

[0018] The application also provides a preparation method of the flexible full-biodegradable Janus nanofiber membrane for oil-water separation as described above, comprising the following preparation steps: a. preparing an electrospinning solution: dissolving polybutylene adipate terephthalate in a mixed solvent prepared from hexafluoroisopropanol and N,N-dimethylformamide at a volume ratio of 9:1, magnetically stirring for a period of time until completely dissolved to obtain a PBAT spinning solution; dissolving polylactic acid in a mixed solvent prepared from hexafluoroisopropanol and N,N-dimethylformamide at a volume ratio of 9:1, magnetically stirring for a period of time until completely dissolved to obtain a PLA spinning solution; b. parallel electrospinning: adding the two spinning solutions obtained in step a into double-channel push injectors, controlling the electrospinning conditions, and continuously and stably electrospinning by the method of double-channel parallel electrospinning to obtain a composite nanofiber membrane with Janus structure; c. hydrophilic modification of the composite nanofiber membrane: c1. preparing a hydrophilic modifier: adding vinyltriethoxysilane and 1-vinyl-2-pyrrolidone into a reaction solvent N,N-dimethylacetamide, stirring thoroughly, then adding an initiator azobisisobutyronitrile, and then heating to 80-100 DEG C for continuous reaction to obtain a hydrophilic modifier; c2. hydrophilic modification: immersing the composite nanofiber membrane prepared in step b in the hydrophilic modifier to obtain a hydrophilic nanofiber membrane through hydrophilic modification.

[0019] The hydrophilic nanofiber membrane of the application is stably prepared through the controllable parallel electrospinning technology, and the electrospinning can directly and continuously prepare a nanofiber membrane with high specific surface area and high porosity, and the process is flexible and the material compatibility is wide, thereby providing a guarantee for the wide application of the membrane material.

[0020] As a limitation of the above technical solution, the concentration of the PBAT spinning solution in step a is 180 mg / mL, and the concentration of the PBAT spinning solution is 150 mg / mL; and / or, the parallel electrospinning conditions in step b are a voltage of 15 KV, a push speed of 1 mL / h, a double-needle push speed ratio of 1:1, a receiving distance of 20 cm, a drum rotation speed of 400 rpm, and a parallel electrospinning time of 12 h.

[0021] As a limitation of the above technical solutions, in step c1, 2.75 g of vinyltriethoxysilane and 3.75 g of 1-vinyl-2-pyrrolidone are added to 100 mL of N,N-dimethylacetamide, and after stirring for 1 h, an initiator azobisisobutyronitrile is added, and heating to 80 DEG C is continued for 12 h to obtain a hydrophilic modifier; and / or, in step c2, the hydrophilic modifier is mixed and diluted with water at a volume ratio of 1.5:1, and then the composite nanofiber membrane is immersed in the diluted hydrophilic modifier for 2 h, and then transferred to 60 DEG C water for 12 h, and the hydrophilic modification is completed.

[0022] Further improve the operation conditions of each step in the preparation, provide a complete and stable preparation method.

[0023] In summary, the present application selects two kinds of compatible degradable polymers to prepare the spinning solution, spins the Janus structure fiber with different components on both sides through double-channel side-by-side electrospinning, and then performs hydrophilic modification to obtain the Janus structure nanofiber membrane with high porosity and flexible characteristics, and clear interface wettability difference, which can realize water phase selective permeation when contacting with oil-water mixture, achieves high oil-water separation rate, has good reusability, and has complete biodegradability and environmental friendliness. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1 is a schematic diagram of the double-channel side-by-side electrospinning method for preparing the fully biodegradable Janus composite nanofiber membrane provided by the embodiment.

[0025] Figure 2 is a schematic diagram of the composite nanofiber membrane prepared by the embodiment.

[0026] Figure 3 is a transmission electron microscope image of the composite nanofiber membrane prepared by the embodiment.

[0027] Figure 4 is an infrared contrast image of the composite nanofiber membrane, the hydrophilic nanofiber membrane and the hydrophilic modifier prepared by the embodiment.

[0028] Figure 5 is a tensile test contrast image of the composite nanofiber membrane, the PLA fiber membrane and the PBAT fiber membrane prepared by the embodiment.

[0029] Figure 6 is a UV test image of the hydrophilic nanofiber membrane prepared by the embodiment for separating the water-toluene emulsion.

[0030] Figure 7 is a flux test result image of the composite nanofiber membrane prepared by the embodiment for separating the water-toluene emulsion.

[0031] Figure 8Figure is the water-in-toluene emulsion flux test result graph of the hydrophilic nanofiber membrane prepared in the example before and after tensile regulation.

[0032] Figure 9 Figure is the scanning electron microscope graph of the ethyl cellulose fiber obtained by the single spinning of the ethyl cellulose spinning solution in Comparative Example 1.

[0033] Figure 10 Figure is the scanning electron microscope graph of the PAN fiber obtained by the single spinning of the PAN spinning solution in Comparative Example 1.

[0034] Figure 11 Figure is the scanning electron microscope graph of the fiber obtained by the parallel electrospinning of the PBAT and PLA spinning solution prepared with the mixed solvent of chloroform and DMF for one minute in Comparative Example 2. DETAILED DESCRIPTION

[0035] The technical solutions of the present application will be described clearly and completely below in combination with the embodiments. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by those skilled in the art without creative labor fall within the protection scope of the present application.

[0036] The experimental methods in the following examples and comparative examples are all conventional methods, unless otherwise specified. The raw materials or test materials used are all typical products purchased on the market, unless otherwise specified. The quantitative tests in the following examples and comparative examples are all set up with three repeated experiments, and the results are averaged.

[0037] Example

[0038] A hydrophilic fully biodegradable Janus nanofiber membrane prepared by a double-channel parallel electrospinning method as shown in Figure 1 The specific preparation operation is as follows.

[0039] a. Preparation of electrospinning solution: dissolve the degradable polymer PBAT in the mixed solvent prepared by HFIP and DMF at a volume ratio of 9:1, and magnetically stir for a period of time until completely dissolved to obtain a PBAT spinning solution with a concentration of 180 mg / mL; dissolve the degradable polymer PLA in the mixed solvent prepared by HFIP and DMF at a volume ratio of 9:1, and magnetically stir for a period of time until completely dissolved to obtain a PLA spinning solution with a concentration of 150 mg / mL.

[0040] b. Side-by-side electrospinning: the two kinds of spinning solutions obtained in step a are respectively added into double-channel push syringes, the electrospinning voltage is controlled at 15 KV, the push speed is 1 mL / h, the double-needle push speed ratio is 1:1, the receiving distance is 20 cm, the drum rotation speed is 400 rpm, and the method of double-channel side-by-side electrospinning is used to continuously and stably electrospin for 12 h to obtain a Janus composite nanofiber membrane with uniform structure and clear two-phase distribution. The structural schematic diagram of the composite nanofiber membrane is shown in Figure 2 , the composite nanofiber membrane is observed by transmission electron microscopy, as shown in Figure 3 , which shows that the Janus structure PLA / PBAT side-by-side fiber is successfully prepared.

[0041] c. Hydrophilic modification of the composite nanofiber membrane: c1. Preparation of a hydrophilic modifier: 2.75 g of VTES and 3.75 g of NVP are respectively weighed and added into 100 mL of DMAC, 0.1 g of an initiator AIBN is added after stirring for 1 h, and then heated to 80℃ for 12 h of continuous reaction to obtain a hydrophilic modifier; c2. Hydrophilic modification: the Janus structure composite nanofiber membrane prepared in step b is immersed in the hydrophilic modifier diluted by mixing the hydrophilic modifier prepared in step c1 with water at a volume ratio of 1.5:1 for 2 h, and then transferred to 60℃ water for 12 h of standing to obtain a hydrophilic nanofiber membrane.

[0042] Regarding the preparation conditions, such as the concentrations of the two kinds of spinning solutions, the electrospinning condition parameters, and the reaction time, they can be adjusted within the limited range given in the summary of the invention according to actual needs to provide a composite nanofiber membrane and a hydrophilic nanofiber membrane that meet the performance requirements.

[0043] The composite nanofiber membrane (referred to as a composite membrane in the figure), the hydrophilic nanofiber membrane (referred to as a hydrophilic membrane in the figure), and the hydrophilic modifier prepared above are respectively subjected to Fourier-infrared detection, as shown in the infrared spectrum of Figure 4 , compared with the composite nanofiber membrane, the hydrophilic nanofiber membrane has an intensity increase or a peak shape change in the 930~970 cm -1 region, which provides evidence for the formation of Si-OH; there is a strong absorption peak near 1630~1680 cm -1 , which is an indirect manifestation of the incorporation of NVP. It is thus shown that the hydrophilic groups are successfully grafted or covered on the composite nanofiber membrane through hydrophilic modification.

[0044] Tensile tests are performed on the composite nanofiber membrane and PLA fiber membranes (obtained by electrospinning using a PLA spinning solution) and PBAT fiber membranes (obtained by electrospinning using a PBAT spinning solution) to test the stress and strain, and the results are as shown in Figure 5As shown, the composite nanofiber membrane adjusts the mechanical properties between PLA fibers and PBAT fibers to some extent, prompting the stress and strain values of both to remain in a moderate range, avoiding extreme changes in performance.

[0045] The hydrophilic nanofiber membrane was used for the separation of toluene-in-water emulsion for UV test, as shown in Figure 6 As shown, the UV spectrum of the oil-in-water emulsion respectively gives 100 mL of toluene-in-water emulsion with 1.0 mL, 0.8 mL, and 0.6 mL of toluene, to prove that the characteristic peak of toluene appears at 261 nm. In addition, a toluene-in-water emulsion with a concentration of 10 mL / L was used for the experiment, and the absorbance of the emulsion before separation was 1.75 (i.e., C0), and the absorbance after separation using the hydrophilic nanofiber membrane decreased to 0.05 (i.e., C1, indicated as split liquid in Figure 6 According to the change in absorbance, the separation efficiency S of this oil-water separation can be calculated as (C0-C1) / C0*100%, and the efficiency of the hydrophilic nanofiber membrane is calculated to be 97.1%.

[0046] In order to verify the effect of hydrophilic modification, we conducted a flux test of the composite nanofiber membrane before hydrophilic modification for the separation of toluene-in-water emulsion, and the results are shown in Figure 7 As shown, the optimal flux of the membrane without hydrophilic modification is about 450 L / m 2 ·h -1 ; at the same time, the flux test of the hydrophilic nanofiber membrane obtained after hydrophilic modification for the separation of toluene-in-water emulsion was also conducted, and the results are shown in Figure 8 As shown, the flux after hydrophilic modification is significantly improved, reaching 1000 L / m 2 ·h -1 , forming a clear contrast. Thus, it is proved that the composite nanofiber membrane without hydrophilic modification has a small flux and a poor speed of processing oil-in-water emulsion. After hydrophilic modification, the flux of the membrane is significantly increased, indicating that the hydrophilic modifier plays an important role in improving the performance of the membrane.

[0047] In addition, Figure 8 The flux test results of the separation of toluene-in-water emulsion under the normal state of the hydrophilic membrane and under the stretched state of the hydrophilic membrane are also given. As can be seen, after moderate stretching of the nanofiber membrane, the separation flux of toluene is significantly improved, reaching a maximum of 2900 L / (m -2 ·h -1 ), which is much higher than the flux value under the unstretched state, indicating that the Janus structure PLA / PBAT hydrophilic nanofiber membrane prepared by double-channel side-by-side electrospinning can significantly improve the flexibility of the nanofiber membrane.

[0048] Comparative Example 1 This comparative example involves the selection of two polymers used for side-by-side electrospinning.

[0049] Firstly, it is determined to use biodegradable material PLA as the main material, dissolved in HFIP and DMF mixed solvent with a volume ratio of 9:1 to prepare a spinning solution with a concentration of 140 mg / mL, and another biodegradable material is selected as an auxiliary material for parallel electrospinning.

[0050] The preliminary attempt is to use ethyl cellulose as an auxiliary material, and ethyl cellulose spinning solution is prepared by using trichloromethane single solvent, with a concentration of 140 mg / mL, the electrospinning voltage is controlled at about 12kv, the spinning distance is 20cm, and the injection speed is 1mL / h. The scanning electron microscope image of the ethyl cellulose fiber spun is shown in Figure 9 However, during the parallel electrospinning process, when the PLA spinning solution contacts with the ethyl cellulose spinning solution, it causes the needle to be blocked, and thus the spinning cannot continue.

[0051] The attempt is to use polyacrylonitrile PAN as an auxiliary material, and PAN is dissolved in single DMF solvent to prepare a PAN spinning solution with a concentration of 120 mg / mL. The electrospinning voltage is controlled at about 12kv, the spinning distance is 20cm, and the injection speed is 1mL / h. The scanning electron microscope image of the PAN fiber spun is shown in Figure 10 However, during the parallel electrospinning process, when the PLA spinning solution contacts with the PAN spinning solution, they react, causing instantaneous precipitation of solid and causing the needle to be blocked, and thus the spinning cannot continue.

[0052] After a series of experiments, PLA and PBAT are selected as the two polymers for parallel electrospinning. Not only is the parallel spinning of the two fully biodegradable polymers successfully achieved, but PBAT also provides good flexibility, effectively neutralizing the mechanical properties of PLA, thereby improving the stability of the spinning process and the performance of the final product.

[0053] Comparative Example 2 This comparative example relates to the selection of solvents for two polymer spinning solutions.

[0054] Common PLA and PBAT spinning solvents include dimethyl sulfoxide DMSO, N,N-dimethylacetamide DMAC, N-methyl pyrrolidone NMP, etc. These solvents are tried to be used to prepare spinning solutions. The experimental results show that these solvents cannot effectively dissolve PLA or PBAT at room temperature. Although dissolution can be achieved by heating and stirring, when the solution cools to room temperature, the raw materials will precipitate solid, and thus the spinning cannot continue. Even if a heating device is used during the spinning process, this problem cannot be effectively solved.

[0055] The commonly used solvent combination of the PLA spinning solution is generally recorded in the existing related literature to include chloroform, dichloromethane and DMF, and the most common chloroform and DMF are used for the preparation of the spinning solution in the experiment, and the volume ratio is 9:1, 8:2, 7:3 (when the chloroform is less than six, the PLA cannot be dissolved), the mixed solvent with the three proportions is used for the electrospinning of the PLA, the voltage is controlled to be about 12kv, the spinning distance is 20cm, the injection speed is 1mL / h, and the rolling speed is 400rmp, and it is found that it cannot support a long-time stable spinning process. Specifically, after spinning for about one minute, the needle blockage phenomenon often occurs.

[0056] In the experiment, the mixed solvent prepared by chloroform and DMF in a volume ratio of 9:1 is used as the solvent of the two polymer spinning solutions, and the PBAT spinning solution with a concentration of 180mg / mL and the PLA spinning solution with a concentration of 150mg / mL are prepared, and the two spinning solutions are respectively added to the double-channel push injector, and the composite nanofiber membrane is spun under the same electrospinning condition parameters as in the embodiment.

[0057] In the side-by-side spinning process, the instability of the spinning is observed, the needle is blocked due to the too fast volatilization of the solvent, and the continuity of the spinning is affected, although the spinning parameters are adjusted and optimized, the problem cannot be effectively improved, and the spinning duration is only about one minute. Figure 11 The SEM image of the fiber when the spinning time is one minute is shown, and due to the needle blockage problem, the obtained nanofiber presents the characteristics of uneven thickness; in addition, the bifurcation phenomenon also occurs in the spinning process, which further causes the side-by-side structure to fail to be successfully formed.

[0058] After a series of experiments, the mixed solvent prepared by HFIP and DMF in a volume ratio of 9:1 is selected as the solvent of the two polymer spinning solutions, which not only effectively solves the needle blockage problem in the spinning process, but also significantly improves the stability of the spinning, and becomes an ideal spinning solvent combination.

[0059] In summary, the two kinds of compatible degradable polymer spinning solutions are used, and the nanofiber membrane with good mechanical flexibility, complete biodegradability and excellent oil-water selective permeability is successfully prepared through a simple side-by-side electrospinning operation, and is suitable for high-efficiency oil-water separation applications.

[0060] Please note that the technical features of the above embodiments can be combined in any manner, and for the sake of brevity, not all possible combinations of the technical features in the above embodiments are described, however, as long as the combinations of the technical features do not contradict each other, they should be considered as within the scope of the present disclosure. The above embodiments only express several implementation manners of the present application, which are described in a more specific and detailed manner, but should not be understood as a limitation on the patent scope of the present application. It should be noted that for those skilled in the art, some modifications and improvements can be made without departing from the concept of the present application, and these are within the scope of the present application. Therefore, the patent protection scope of the present application should be subject to the appended claims.

Claims

1. A flexible, fully biodegradable Janus nanofiber membrane for oil-water separation, characterized in that: A composite nanofiber membrane with a Janus structure is spun from two biodegradable polymer spinning solutions by parallel electrospinning. After hydrophilic modification, a hydrophilic nanofiber membrane is obtained for use as an oil-water separation membrane, namely a flexible fully biodegradable Janus nanofiber membrane for oil-water separation. The two biodegradable polymers selected for the spinning solution are any two of the following that are compatible with each other and can be successfully used for parallel electrospinning: polylactic acid, poly(ε-caprolactone), polybutylene succinate, poly(3-hydroxyalkanoate), polybutylene adipate, poly(3-hydroxybutyrate), polyacrylic acid, and polyvinyl alcohol. The solvent selected for the spinning solution is at least one of the following: N,N-dimethylformamide, dichloromethane, N-methylpyrrolidone, hexafluoroisopropanol, N,N-dimethylacetamide, chloroform, and carbon tetrachloride. The hydrophilic modifier used in hydrophilic modification is prepared by using an initiator from a compound containing a hydrophilic group. The compound containing the hydrophilic group is at least one of 1-vinyl-2-pyrrolidone, acrylic acid, acrylamide, vinyltriethoxysilane, acrylamide, and chloroacetic acid.

2. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 1, characterized in that: The two biodegradable polymers used in the spinning solution are polylactic acid and polybutylene terephthalate; and / or, the solvents used in the spinning solution are mixed solvents prepared from hexafluoroisopropanol and N,N-dimethylformamide.

3. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 2, characterized in that: The solvents used in the spinning solution are a mixture of hexafluoroisopropanol and N,N-dimethylformamide in a volume ratio of 9:

1.

4. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 1, characterized in that: The concentrations of the two biodegradable polymers in the spinning solution were both 100 mg / mL to 220 mg / mL.

5. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 1, characterized in that: The hydrophilic modifier is prepared by adding vinyltriethoxysilane and 1-vinyl-2-pyrrolidone to the reaction solvent N,N-dimethylacetamide, stirring thoroughly, adding an initiator, and then heating to 80~100℃ to react. Preferably, the ratio of vinyltriethoxysilane, 1-vinyl-2-pyrrolidone, N,N-dimethylacetamide and initiator is 1~5g:2~6g:100~200mL:0.1~1g.

6. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 5, characterized in that: The initiator is selected from one of the following: hydrogen peroxide, sulfur tetrafluoride, azobisisobutyronitrile, azobisisobutyronitrile, ammonium persulfate, benzoyl peroxide, and dicumyl peroxide.

7. The flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 1, characterized in that: The conditions for parallel electrospinning are: voltage 10~15KV, feed speed 0.8~1.5mL / h, dual needle feed speed ratio of 1:1, receiving distance of 15~20cm, and roller rotation speed of 300~600rpm.

8. The method for preparing a flexible, fully biodegradable Janus nanofiber membrane for oil-water separation as described in any one of claims 1 to 7, characterized in that, The preparation steps include the following: a. Preparation of electrospinning solution: Dissolve polybutylene terephthalate (PBAT) in a mixed solvent prepared by hexafluoroisopropanol and N,N-dimethylformamide in a volume ratio of 9:1, and stir magnetically for a period of time until completely dissolved to obtain PBAT spinning solution; also dissolve polylactic acid in a mixed solvent prepared by hexafluoroisopropanol and N,N-dimethylformamide in a volume ratio of 9:1, and stir magnetically for a period of time until completely dissolved to obtain PLA spinning solution; b. Parallel electrospinning: The two spinning solutions obtained in step a are added to a dual-channel push injector, and the electrospinning conditions are controlled. Through the dual-channel parallel electrospinning method, continuous and stable electrospinning is carried out to obtain a composite nanofiber membrane with a Janus structure. c. Hydrophilic modification of composite nanofiber membranes: c1. Preparation of hydrophilic modifier: Vinyltriethoxysilane and 1-vinyl-2-pyrrolidone are added to the reaction solvent N,N-dimethylacetamide, stirred thoroughly, and then the initiator azobisisobutyronitrile is added. The mixture is then heated to 80~100℃ and the reaction is continued to obtain the hydrophilic modifier. c2. Hydrophilic modification: The composite nanofiber membrane prepared in step b is impregnated in a hydrophilic modifier to obtain a hydrophilic nanofiber membrane after hydrophilic modification.

9. The method for preparing the flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 8, characterized in that: In step a, the concentration of PBAT spinning solution is 180 mg / mL, and the concentration of PLA spinning solution is 150 mg / mL; and / or, in step b, the parallel electrospinning conditions are: voltage 15 KV, feed speed 1 mL / h, dual needle feed speed ratio of 1:1, receiving distance of 20 cm, roller rotation speed of 400 rpm, and parallel electrospinning time of 12 h.

10. The method for preparing a flexible, fully biodegradable Janus nanofiber membrane for oil-water separation according to claim 1, characterized in that: In step c1, 2.75 g of vinyltriethoxysilane and 3.75 g of 1-vinyl-2-pyrrolidone were added to 100 mL of N,N-dimethylacetamide and stirred for 1 h. Then, the initiator azobisisobutyronitrile was added, and the mixture was heated to 80 °C and reacted for 12 h to obtain a hydrophilic modifier. In step c2, the hydrophilic modifier was diluted with water at a ratio of 1.5:

1. The composite nanofiber membrane was then immersed in the diluted hydrophilic modifier for 2 h and then transferred to water at 60 °C and allowed to stand for 12 h to complete the hydrophilic modification.

Citation Information

Cited By

  • Breathable isolating membrane and preparation method thereof

    CN122185614A